2000
DOI: 10.1126/science.287.5458.1647
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the Inositol Trisphosphate Receptor for Activation of Store-Operated Ca 2+ Channels

Abstract: The coupling mechanism between endoplasmic reticulum (ER) calcium ion (Ca2+) stores and plasma membrane (PM) store-operated channels (SOCs) is crucial to Ca2+ signaling but has eluded detection. SOCs may be functionally related to the TRP family of receptor-operated channels. Direct comparison of endogenous SOCs with stably expressed TRP3 channels in human embryonic kidney (HEK293) cells revealed that TRP3 channels differ in being store independent. However, condensed cortical F-actin prevented activation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
512
10

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(557 citation statements)
references
References 23 publications
34
512
10
Order By: Relevance
“…Application of the DAG analogue 1-oleoyl-2-acetyl-sn-glycerol (100 M) induced a small Ca 2ϩ influx in parental cells and non-transfected CJ-5 control cells (46). However, no Ca 2ϩ increase compared with control CJ-5 cells was observed in TRPC3-transfected CJ-5 cells (three experiments, n ϭ 194 green cells, data not shown) indicating that TRPC3 channels in Jurkat T-cells are not activated by DAGs, which is in contrast to other studies overexpressing TRPC3 in Chinese hamster ovary cells (50) and HEK 293 cells (23).…”
Section: Trpc3 Rescues Insp 3 -Induced Currents In the Mutantcontrasting
confidence: 53%
See 1 more Smart Citation
“…Application of the DAG analogue 1-oleoyl-2-acetyl-sn-glycerol (100 M) induced a small Ca 2ϩ influx in parental cells and non-transfected CJ-5 control cells (46). However, no Ca 2ϩ increase compared with control CJ-5 cells was observed in TRPC3-transfected CJ-5 cells (three experiments, n ϭ 194 green cells, data not shown) indicating that TRPC3 channels in Jurkat T-cells are not activated by DAGs, which is in contrast to other studies overexpressing TRPC3 in Chinese hamster ovary cells (50) and HEK 293 cells (23).…”
Section: Trpc3 Rescues Insp 3 -Induced Currents In the Mutantcontrasting
confidence: 53%
“…In other cell types, there is evidence that TRPC3 channel activity depends upon interaction with InsP 3 and/or ryanodine receptors (21)(22)(23)(24)(25)(26). This activity seems to be modulated by the binding of Ca 2ϩ /calmodulin (24,27) and by the binding of phospholipase C␥ (28).…”
mentioning
confidence: 99%
“…Although evidence from several laboratories showed that IP 3 R coupling with TRPC can trigger Ca 2ϩ entry, the mechanisms responsible for this critical association event are not clear (23,25,34,(61)(62)(63)(64). Models involving chemical and conformation coupling have been suggested (1, 11, 14 -16, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this model fails to explain Ca 2ϩ entry by TRPC1 as these channels have been shown to be localized within intracellular membranes (35). These inconsistencies suggest that coupling involves other events such as translocation and docking of IP 3 R and TRPC1 at the plasma membrane (1,23,24,34). Thus, it is possible that proteins capable of trafficking IP 3 R and TRPC1 to the membrane induce association of components of the complex and trigger Ca 2ϩ entry.…”
mentioning
confidence: 90%
“…Although these drugs can have multiple targets (Collin et al, 2005), 2-APB has proven to be an effective inhibitor of IP3-mediated calcium release in intact cells of vertebrates and invertebrates (Maruyama et al, 1997;Ma et al, 2000;Koganezawa and Shimada, 2002) and has not been found to alter either agonist-mediated IP3 production or IP3 binding to its receptor (Maruyama et al, 1997;Ma et al, 2000). Both compounds effectively blocked KAR-induced changes in IPSCs.…”
Section: Involvement Of Ca 2+ and Ip3rsmentioning
confidence: 99%